Using Coherent Speech Types to Develop the Thinking of Primary School Students - Zeripboyeva Kumushoy Jamoladdin qizi (Academia One, 2024)
This article examines the effectiveness of using coherent speech types in developing the thinking of primary school students.
Keywords: coherent speech; vocabulary; thinking